2006
DOI: 10.1038/sj.onc.1209657
|View full text |Cite
|
Sign up to set email alerts
|

Genomic loss and epigenetic silencing of very-low-density lipoprotein receptor involved in gastric carcinogenesis

Abstract: Homozygous loss in the genomic sequence, a mechanism for inactivating tumor-suppressor genes (TSGs) in cancer, has been used as a tag for the identification of novel TSGs, and array-based comparative genomic hybridization (array-CGH) has a great potential for high-throughput identification of this change. We identified a homozygous loss of the very-low-density lipoprotein receptor (VLDLR) gene (9p24.2) from genome-wide screening for copynumber alterations in 32 gastric cancer (GC) cell lines using array-CGH. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 36 publications
2
37
1
Order By: Relevance
“…Quantitative measurement of DNA copy numbers across the genome has revealed various oncogenes (Tanami et al, 2005) or tumour suppressor genes (Takada et al, 2005(Takada et al, , 2006) that had not been detected by earlier techniques. In addition, the higher resolution of array-CGH has allowed precise mapping of the boundaries of the gained and lost regions, thereby helping to elucidate the clonal relationship between multifocal tumours (Shelley Hwang et al, 2004;Wa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurement of DNA copy numbers across the genome has revealed various oncogenes (Tanami et al, 2005) or tumour suppressor genes (Takada et al, 2005(Takada et al, , 2006) that had not been detected by earlier techniques. In addition, the higher resolution of array-CGH has allowed precise mapping of the boundaries of the gained and lost regions, thereby helping to elucidate the clonal relationship between multifocal tumours (Shelley Hwang et al, 2004;Wa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Array-based CGH (array-CGH) technique allows high-throughput and quantitative analyses of copy-number changes at high-resolution throughout the genome, providing many advantages, including the identification of homozygous loss, over conventional methods (Snijders et al, 2001;Inazawa et al, 2004), although the resolution fully depends on the type of array. Indeed, our previous array-CGH studies using inhouse bacterial artificial chromosome-(BAC-)/P1-derived artificial chromosome-(PAC-) based arrays (BAC/ PAC-arrays) have successfully mapped complete genetic losses, allowing the rapid identification of candidate TSGs inactivated mainly by genetic and/or epigenetic mechanisms (Sonoda et al, 2004;Izumi et al, 2005;Takada et al, 2005bTakada et al, , 2006Imoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism by which RELN contributes to tumorigenicity remains to be elucidated, the data presented in this study, together with the recent finding that the VLDLR gene, whose product functions as the receptor for RELN, is also epigenetically silenced in GC (9), clearly suggest that disruption of the RELN pathway is involved in gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 74%
“…The recent observation that the VLDLR gene is frequently silenced by promoter hypermethylation in GC suggested that disruption of the RELN pathway may be involved in gastric carcinogenesis (9). The RELN gene harbors a long CpG-rich promoter region (10) and expression of RELN is regulated by the methylation status of the promoter (11).…”
Section: Introductionmentioning
confidence: 99%